STUDY OF AMYLOSE CONTENT THAT AFFECT GEL CONSISTENCY (GC) AND THE TEXTURE CHARACTERISTICS OF VARIOUS RICE VARIETIES IN CULTIVATION AREAS, NAKHON SAWAN PROVINCE - Sirinon, Sirikanjana; Pechampai, Natthapong (Srinakharinwirot University Journal of Sciences and Technology, 2024)
Study of amylose content that affects the viscosity of the starch gel and texture characteristics of various rice varieties in the growing areas of Nakhon Sawan Province. The research aimed to compare the amylose content, influencing the viscosity of starch gel and the texture of rice across various varieties. Using spectroscopy and the gel consistency (GC) method, the study analyzed 26 rice samples representing different varieties. The focus was on comparing the amylose content that affects rice starch gel viscosity. During the dry-season cultivation RD31 stood out with the highest amylose content (18.98 percentage) and a medium gel consistency of 42.17 millimeters, indicating a rice variety with moderate hardness. The wet-season cultivation Niaw Wan and Niaw Dang, both with low amylose content (8.95 and 8.94 percentage, respectively), demonstrated soft rice textures with gel consistencies of 74.30 and 75.47 millimeters, respectively, which is rice that has a low level of hardness or softness. This shows that in the wet-season cultivation, Niaw Wan and Niaw Dang have higher starch gel viscosity values than the dry-season cultivation RD31, which is significantly different (p<0.05). This research contributes to understanding the quality characteristics of rice, particularly in terms of rice texture, which can have culinary applications.